Rights Based Management and the Reform of the Common Fisheries Policy: The Debate - Coelho, Manuel Pacheco (2013)
Besides some interesting results, the Common Fisheries Policy has not delivered a sustainable use of fish resources. Recently, the Pew Environment Group released a study that finds that E. U. fisheries have failed to reduce fleet capacity thus exerting fishing pressure on stocks at two/three time sustainable levels. Overcapacity and overcapitalisation of the sector was identified as the principal failure of the CFP. This conclusion may be well important in the CFP reform (2012) and put again the discussion about the tools that can be used to get sustainable management and better cohesion. The idea of creating markets for fishing rights as a means of internalising the externalities derived from the common property nature of fisheries have received considerable attention from the founding fathers of Law and Economics and Fisheries Economics such as Coase, Scott and Christy. Rights Based Management schemes have already been experimented in some specific fisheries and localizations. These experiences have a lot of teaching results about good practices of sustainable fisheries management and also about the limitations/risks of these tools. These conclusions are fundamental to explore the feasibility of these tools. The purpose of our study is to enter this debate and investigate the feasibility of introducing these new management regimes in the CFP.